Avaliação ambiental, caracterização da qualidade de água e transporte de sedimentos da bacia hidrográfica do Ribeirão Monjolo Grande (SP) - Spatti Junior, Eder Paulo [UNESP] (2011)
The pressure on natural resources, especially on water resources has increased significantly as is increased demand for space, reflecting the increasing degradation of water sources in different scales. Thus, it is of great value to perform work that can support the planning and subsequent management of natural resources with a view to environmental sustainability. In this context, this work performs the environmental assessment, characterization of water quality and sediment transport in the Monjolo Grande watershed, located in Ipeúna (SP). The simplified environmental evaluation indicated that while the area is totally rural environment, with 50% of the 20 points classified as high environmental impacts, causing great loss of vegetation and maintenance of erosion. The water quality evaluated the variation of physicochemical parameters, the concentration of major cations and anions, the suspended solids (particulate and dissolved), and total and dissolved concentrations of Al, Fe, Mn, Ba, Pb, Cu, Zi, Ni and Cd. The water quality evaluated the variation of physicochemical parameters, the concentration of major cations and anions, the suspended solids (particulate and dissolved) in addition to the concentration of Al, Fe, Mn, Ba, Pb, Cu, Zi, Ni and Cd. Such quantification framed the surface waters of the Monjolo Grande as Class 2, according to the CONAMA resolution 357. The transport of sediment showed a removal of 476 ton/km²/year, and the method of Colby indicated that most sediment is transported by drag, by the characteristics of the sediments, predominantly in the sand fraction